THE IMPLEMENTATION OF PEER ASSISTED LEARNING STRATEGY (PALS) IN TEACHING READING COMPREHENSION (A Mixed Method Study at Tenth Grade in One of Senior High Schools in Ciamis) - Suci Fitriani; Wawan Tarwana (Universitas Galuh, 2020)
ABSTRACTThis article is aimed at finding out the effectiveness on implementing Peer Assisted Learning Strategy (PALS) in teaching reading comprehension and investigating the students’ perceptions on implementing this method. This study used mixed method study which employed quantitative and qualitative research design. Quantitative data were analyzed by using pre-test and post-test, the qualitative data was analyzed by using close ended questionnaire. The population of this study were the students of tenth grade in one of senior high school in Ciamis and the researcher selected a particular class, which was sciences for a total 38 students as the sample. Based on statistical result, after implementing PALS in teaching reading comprehension of recount text, the significant improvement of reading comprehension showed from result of pre-test and post-test. In the pre-test the average score of students was 71.84, and in the post test the average score of students was 87.37. Thus, the use of Peer Assisted Learning Strategy (PALS) is effective in teaching reading comprehension of recount text. In addition, from the analysis of close ended questionnaire, the students was gave a positive responses towards PALS in teaching reading comprehension of recount text. In conclusion, the student‘s reading comprehension was effective and the students were able to comprehend the text through PALS. Based on these finding, it is recommended for English teachers to implementing PALS to improve students’ reading comprehension. Keywords: peer assisted learning strategy, reading comprehension, recount text